Expanding the Phenotype of Frontotemporal Lobar Degeneration With FUS-Positive Pathology (FTLD-FUS). Issue 7 (1st June 2020) - Chornenka, Karina; Hirsch-Reinshagen, Veronica; Perez-Rosendahl, Mari; Feldman, Howard; Segal-Gidan, Freddi; Vinters, Harry V; Mackenzie, Ian R
Abstract: Atypical frontotemporal lobar degeneration with ubiquitin-positive inclusions (aFTLD-U) is an uncommon cause of frontotemporal dementia characterized by fused in sarcoma -positive inclusions. It is classified as a subtype of frontotemporal lobar degeneration with FUS pathology. Cases with aFTLD-U pathology typically display an early onset of symptoms and severe psychobehavioral changes in the absence of significant aphasia, cognitive-intellectual dysfunction or motor features. This phenotype is regarded as being sufficiently unusual and consistent as to allow antemortem diagnosis with a high degree of accuracy. In this report, we describe 2 cases with aFTLD-U pathology that broaden the associated phenotype to include later age of onset, milder behavioral abnormalities and early memory and language impairment.